The Role of the Insulin-Like Growth Factor 1 Pathway in Immune Tumor Microenvironment and Its Clinical Ramifications in Gynecologic Malignancies - Yahya, Muna Alemi; Sharon, Shilhav Meisel; Hantisteanu, Shay; Hallak, Mordechai; Bruchim, Ilan (Frontiers in Endocrinology, 2018)
Treatment of patients with gynecologic malignancies diagnosed at advanced stages remains a therapeutic challenge. Survival rates of these patients remain significantly low, despite surgery and chemotherapy. Advances in understanding the role of the immune system in the pathogenesis of cancer have led to the rapid evolution of immunotherapeutic approaches. Immunotherapeutic strategies, including targeting specific immune checkpoints, as well as dendritic cell (DC) immunotherapy are being investigated in several malignancies, including gynecological cancers. Another important approach in cancer therapy is to inhibit molecular pathways that are crucial for tumor growth and maintenance, such as the insulin-like growth factor-1 (IGF1) pathway. The IGF axis has been shown to play a significant role in carcinogenesis of several types of tissue, including ovarian cancer. Preclinical studies reported significant anti-proliferative activity of IGF1 receptor (IGF1R) inhibitors in gynecologic malignancies. However, recent clinical studies have shown variable response rates with advanced solid tumors. This study provides an overview on current immunotherapy strategies and on IGF-targeted therapy for gynecologic malignancies. We focus on the involvement of IGF1R signaling in DCs and present our preliminary results which imply that the IGF axis contributes to an immunosuppressive tumor microenvironment (TME). For the long term, we believe that restoring the TME function by IGF1R targeting in combination with immunotherapy can serve as a new clinical approach for gynecological cancers.